MicroRNA Regulation of SIRT1 - Yamakuchi, Munekazu (Frontiers in Physiology, 2012)
SIRT1 is an NAD-dependent deacetylase that regulates the cellular response to stressors. SIRT1 is intensively studied as a potental regulator of cellular metabolism and longevity. Pathways of SIRT1 regulation may lead to a greater understanding of metabolism and aging. Post-transcriptional regulation of SIRT1 is mediated by two classes of molecules, RNA-binding proteins and non-coding small RNAs. MicroRNAs (miRNAs) are short non-coding RNAs that regulate target gene expression in a post-transcriptional manner. More than 10 miRNAs modulate SIRT1 expression, including miR-34a. MiR-34a induces colon cancer apoptosis through SIRT1, and miR-34a also promotes senescence in endothelial cells via SIRT1. In this review, I describe the impact of miRNAs on SIRT1. First I outline the background of SIRT1 and miRNAs, then I demonstrate the mechanism by which several key miRNAs alter SIRT1 levels. I focus on the modulation of SIRT1 function by these miRNAs in the cardiovascular systems, metabolic pathway and cancer. Next I address the regulatory mechanism of SIRT1 by another important molecule, a RNA-binding protein HuR, which associates with SIRT1 mRNA and regulates its expression.